CURRENT STATUS OF THE BENCHMARK DATABASE BEMEDA - L. E. Budde; J. Schmidt; T. Kullmann; D. Iwaszczuk (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
Open science is an important attribute for developing new approaches. Especially, the data component plays a significant role. The FAIR principle provides a good orientation towards open data. One part of FAIR is findability. Thus, domain specific dataset search platforms were developed: the Earth Observation Database and our Benchmark Metadata Database (BeMeDa). In addition to the search itself, the datasets found by this platforms can be compared with each other with regard to their interoperability. We compare these two platforms and present an update of our platform BeMeDa. This update includes additional location information about the datasets and a new frontend design with improved usability. We rely on user feedback for further improvements and enhancements.